Initial adaptation of the OnTrack coordinated specialty care model in Chile: An application of the Dynamic Adaptation Process - Le, PhuongThao D.; Choe, Karen; Burrone, María Soledad; Bello, Iruma; Velasco, Paola; Arratia, Tamara; Tal, Danielle; Mascayano, Franco; Jorquera, María José; Schilling, Sara; Ramírez, Jorge; Arancibia, Diego; et al. (Frontiers in Health Services, 2022)
Background: In 2005, Chile became the first country in Latin America to guarantee universal free access for the diagnosis and treatment of schizophrenia. A cluster randomized control trial utilizing the Dynamic Adaptation Framework is underway to adapt and test the OnTrack coordinated specialty care model to provide recovery-oriented, person-centered care by a multidisciplinary team for individuals with first episode psychosis (FEP) in Chile. Methods: A qualitative formative research study was conducted to inform the initial adaptation of the OnTrack Chile (OTCH) program. We conducted key informant interviews (n=17) with various stakeholders (policymakers; directors/managers of community mental health centers; mental health professionals) and focus group discussions (n=6) with individuals with FEP and caregivers (n=35 focus group participants total). Data was analyzed using thematic analysis , organized by participants’ perspectives on the benefits, barriers, and recommendations for the key principles, multidiscplinary team, community-based components, and the training and supervision model of OnTrack. Results: Participants expressed enthusiasm and support for OnTrack’s recovery-oriented and person-centered principles of care. Peer specialists and the family psychoeducation and support and supported education and employment components were perceived as aspects that could encourage the promotion of personhood and autonomy development. While many participants lauded the emphasis on shared-decision making and family involvement, some reported reticence, citing that it is culturally normative for patients and families to adopt a passive role in treatment. Participants also highlighted numerous challenges, including infrastructure, human, and financial constraints that should be addressed. Some mental health professionals further conveyed reservations regarding the involvement of peer specialists and the perceived hierarchical structure of the supervision model. Conclusions: OnTrack represents a shift from a biomedical model to a valued, aspirational, person-centered and culturally responsive model that focuses on recovery, shared-decision making and psychosocial care. With the appropriate governmental and agency-level provision of resources and modifications to the program components, particularly regarding the shared decision making framework, family engagement, and the training supervision model, OTCH could be a transformative program for a more comprehensive, evidence-based care for individuals with FEP in Chile.